Performances of fuel injection system in diesel engine using distributor type fuel injection pump / Mohd Nizan Rifai, Shahidan Sudin and Mohamad Sukri Ismail - Rifai, Mohd Nizan; Sudin, Shahidan; Ismail, Mohamad Sukri (Faculty of Mechanical Engineering, 2000)
This project introduced the fuel injection system in diesel engine using distributor type pump. Normally, the vehicle using this pump is “Nissan SD 22 series (104749-4040). The process or principal workings are also introduced in this project. All the component and part must be to know for knowledge the functions. It is included the constructions, operation, governor section (variable speed governor operation, higher speed operation, idle and maximum speed governor), solenoid operation, advance unit, fuel pump timing, and etc. Beside that, fuel pump must calibrate with use “calibration machine” before to applied to the vehicle. The service manual has been prepared primarily for assisting service personal in providing effective service and maintenance of “fuel pump diesel series” for the vehicle. The distributor fuel pumps VE types, which includes for maintenance, adjustments, removal and installation, disassembly and assembly of components, and troubleshooting. All information, illustrations and specifications contained in service manual are based on the latest product information available at the any time. When to removal the all component, keep clean the surround places because the fuel pump components are very sensitive to dirt. Any components have to remove, it is must to remind or put a mark for installing back. The fuel injector is the important component in the fuel injection system. The installation the pump is also sensitive to deposit. It is included the constructions, operation, service injector, inspections, reassembly, and trouble-shooting. Each component in injector, which service must to make adjustment to follow the manual manufacturers. Adjustment to injector depends on manual manufacturer’s fuel pump type. All part in fuel injection pump and injector, we must know the function, formally, a good fuel pump show the reading same with the manual manufacturer’s fuel pump.